Decomposing inequality in household consumption expenditure in Malaysia - Mohsen Ayyash; Siok Kun Sek (Economies, 2020)
This study aims to examine the sources and determinants of consumption expenditure inequality in Malaysia as well as to quantify their proportional contributions to the total explained inequality using the Household Expenditure Survey (HES) data for the year 2014 collected from the Malaysian Department of Statistics (DOSM). The study applies Field's regression-based decomposition method to the log-linear regression model of per capita monthly consumption expenditure. It is found that the model explains about 55.2% of the variability in the logged monthly consumption expenditure per capita. The findings suggest that the size of households, education of household heads, and regional variations are the major contributing factors to consumption expenditure inequality in Malaysia, with household size being among the highest. Other household head characteristics, including ethnicity, strata, and citizenship, have small contributions to the total explained inequality. However, sex and age of household heads contributed negatively to inequality and have inequality decreasing effects, with a negative impact on inequality. A large percentage of unexplained inequality is not captured by these factors, which may be attributed to either unobserved household attributes or residuals. The results are important for policy implications and should be taken into account in formulating future policies, especially those aiming to reduce inequality among the population and thus improving living standards and well-being.
Keywords: 330; consumption expenditure inequality; regression‐ based decomposition; Malaysia